Pain and fertility outcomes post endometriosis surgery at Groote Schuur hospital - Kalwiba, Christian (Department of Obstetrics and Gynaecology, 2023)
Background Endometriosis is characterized by the development of endometrial-like tissue outside of the uterus, which results in a persistent inflammatory response . It is an estrogen-dependent chronic disorder and affects millions of women in their reproductive age. The true incidence is not well known but it is around 6% or more. The clinical presentation of endometriosis varies. Most women will present with secondary dysmenorrhea, dyspareunia, pelvic pain, and infertility. Laparoscopy is the gold standard diagnostic tool for endometriosis, with surgical management being the mainstay in the treatment of endometriosis. Objectives The study's primary objective was to determine the effect of surgery on pain and infertility in women with endometriosis. Secondly, to determine the demographics, severity of endometriosis and laparoscopic complications, recurrence of symptoms and need for repeat surgery. Methodology To achieve the objectives of this research, the study design was a retrospective study. Seventyfive women with endometriosis who attended the reproductive Medicine Unit at Groote Schuur Hospital in Cape Town from January 2016 to December 2018 were analysed. Results Eighty-seven patients were identified with endometriosis from January 2016 to December 2018. Twelve folders could not be retrieved, therefore 75 patients out of the 87 were included in and analysed for this study. Some of the 75 patient files had missing information regarding some of the variables. Post laparoscopic surgery, the pain improved in 90%, 82%, 85% and 61% of patients with a P value < 0.05 at 6 weeks, 6 months, 1 year and 2 years, respectively. Thirty percent of women operated primarily for infertility conceived spontaneously within 2 years. Nine point three percent of patients were reoperated with a mean duration from primary to second surgery of 3 years ± 1.3. More than six percent (6.6%) had intraoperative complications with two patients having ureteric injuries, another two with bowel injuries, and one who had vascular injuries. The prevalence of endometriosis among women undergoing laparoscopic surgeries was 30.6% over the 3-year period. Chronic pelvic pain was the most common symptoms in 86.6% of patients. Dysmenorrhea was reported in 72,6%, 36.5% had dyspareunia, 50% had heavy menstrual bleeding and 53% had primary or secondary infertility. Chronic pelvic pain and infertility were found in 42.67%. Conclusion This study has shown a great improvement in pain post laparoscopic surgery varying from 90% at 6 weeks to 61% at 2 years. About one-third of patients operated on for primarily infertility will conceive spontaneously post-surgical intervention. We recommend a new study with a large sample size in order to determine the improvement and fertility according to the stages of endometriosis.